FISCAL TRANSPARENCY AND DEMOCRATIC GOVERNANCE: THE MEDIATING ROLE OF PUBLIC SECTOR ACCOUNTING SYSTEMS - Ferry Hendro Basuki; Trisna Prasetyaningrum; Alexander Gasperz (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
Fiscal transparency is a key prerequisite for realizing democratic and accountable governance. In the context of modern democracy, fiscal information disclosure serves not only as an instrument for public oversight of state financial management but also as a mechanism to strengthen government legitimacy and increase public participation in the decision-making process. However, the level of effective fiscal transparency is significantly influenced by the quality of the public sector accounting system used by the government. This study aims to examine the relationship between fiscal transparency and democratic governance by positioning the public sector accounting system as a mediating variable. The research method used is a systematic literature review of international scientific journals, reports from international institutions, and relevant policy documents in the fields of public finance, government accounting, and governance. The results of the study indicate that a reliable, standardized, and transparency-based public sector accounting system plays a significant role in bridging the relationship between fiscal openness and strengthening democratic principles, such as accountability, responsiveness, and public oversight. A weak accounting system tends to hinder stakeholders' utilization of fiscal information, thereby reducing the positive impact of fiscal transparency on the quality of democratic governance. This study emphasizes the importance of reforming and strengthening the public sector accounting system as an institutional foundation to support meaningful and sustainable fiscal transparency within a democratic governance framework.